Intratumor microbiota in cancer pathogenesis and immunity: from mechanisms of action to therapeutic opportunities - Wang, Man; Yu, Fei; Li, Peifeng (Frontiers in Immunology, 2023)
Microbial species that dwell human bodies have profound effects on overall health and multiple pathological conditions. The tumor microenvironment (TME) is characterized by disordered vasculature, hypoxia, excessive nutrition and immunosuppression. Thus, it is a favorable niche for microbial survival and growth. Multiple lines of evidence support the existence of microorganisms within diverse types of cancers. Like gut microbiota, intratumoral microbes have been tightly associated with cancer pathogenesis. Intratumoral microbiota can affect cancer development through various mechanisms, including induction of host genetic mutation, remodeling of the immune landscape and regulation of cancer metabolism and oncogenic pathways. Tumor-associated microbes modulate the efficacy of anticancer therapies, suggesting their potential utility as novel targets for future intervention. In addition, a growing body of evidence has manifested the diagnostic, prognostic, and therapeutic potential of intratumoral microorganisms in cancer. Nevertheless, our knowledge of the diversity and biological function of intratumoral microbiota is still incomplete. A deeper appreciation of tumor microbiome will be crucial to delineate the key pathological mechanisms underlying cancer progression and hasten the development of personalized treatment approaches. Herein, we summarize the most recent progress of the research into the emerging roles of intratumoral microbiota in cancer and towards clarifying the sophisticated mechanisms involved. Moreover, we discuss the effect of intratumoral microbiota on cancer treatment response and highlight its potential clinical implications in cancer.